2021
DOI: 10.1186/s12957-021-02324-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hypoxia-inducible factor-1α C1772T/G1790A polymorphisms and head and neck cancer risk: a meta-analysis

Abstract: Objective This meta-analysis was implemented to evaluate the association between hypoxia-inducible factor-1α (HIF-1α) C1772T/G1790A polymorphisms and susceptibility to head and neck cancer (HNC). Material and methods This meta-analysis has been registered on PROSPERO platform (CRD42021257309). The PubMed, Embase and Web of Science databases were searched to retrieve eligible published papers. STATA software was used to calculate the pooled odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our study is retrospective and needs to be corrected for clinical application. Other factors like smoking [45], neoadjuvant chemotherapy [46], heavy alcohol drinking [47], hypoxia [48], aerobic glycolysis [49], and methylation [50] have been discovered to be associated with prognosis of oral cancer, which provides beneficial enlightenments for our future study about IRGPs signature contributing to improve oral cancer outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is retrospective and needs to be corrected for clinical application. Other factors like smoking [45], neoadjuvant chemotherapy [46], heavy alcohol drinking [47], hypoxia [48], aerobic glycolysis [49], and methylation [50] have been discovered to be associated with prognosis of oral cancer, which provides beneficial enlightenments for our future study about IRGPs signature contributing to improve oral cancer outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to wonder about the influence that race could have on HIF-1α expression. Indeed, the level of HIF-1α expression differs among individuals according to the presence or absence of C1772T (C→T mutation) or G1790A (G→A mutation), the region of transcriptional activity and of the binding site to VHL protein (34). Subgroup analyses showed that HIF-1α expression was an unfavorable prognostic factor in PDAC patients from China (26,28,(30)(31)(32), and Japan (27,29,33) with zero heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…When stratified analysis was performed in terms of the source of controls, we found that only the HB population in the recessive model of the IL-17A rs2275913 polymorphism showed no significant relationship with elevated colorectal cancer risk. Since patients with self-underlying diseases were included, potential selection bias was likely to decrease the representativeness of controls in the HB group compared to those in the PB group [ 47 ]. In the models of the IL-17F rs763780 polymorphism, no significant association with colorectal cancer susceptibility was observed in either PB or HB populations.…”
Section: Discussionmentioning
confidence: 99%